Germinação de pólen, floração e frutificação efetiva de cultivares de pessegueiros no sudoeste do Paraná - Barbieri, Claudia Regina (2018)
Because the peach tree is a fruit of a temperate climate, studies are needed in the search for cultivars that adapt and produce well in regions of subtropical climate with milder winters. Thus, the objective of this work was to evaluate the phenology, the production and viability of pollen and the effective fruiting of 16 peach tree cultivars in Dois Vizinhos, southwest of Paraná. The work was developed with peach trees from the fruit growing sector of the Universidade Tecnológica Federal do Paraná, campus Dois Vizinhos, Brazil. Three bifactorial 16 x 2 (cultivars x harvest year; cultivars x storage conditions and; cultivars x pollen incubation times), experiments were carried out in a completely randomized design with four replicates. The evaluated cultivars were: Rubimel, Leonense, Coral, Marli, Charme, Riograndense, Douradão, Chimarrita, Regalo, Kampai, Fascínio, Zilli, Granada, BR-1, Bonão and Eldorado. The harvest years were 2016 and 2017. In experiment 1, pollen production by anther and its in vitro viability were evaluated. In experiment 2, the phenology of flowering and sprouting and the effective fruiting of the plants were evaluated. For the experiment 1, it was concluded that the winter conditions of 2016 were better, promoting greater pollen production; the cultivars Leonense, Rubimel, Douradão and Regalo obtained greater viability of pollen; the storage of the pollen for 60 days at -20 °C, reduces its viability by 42% and, four hours incubation with photoperiod, is sufficient to promote the germination of the pollen. For the experiment 2, it was concluded that in the environmental conditions of Dois Vizinhos - PR, the harvest of 2016 promoted the highest rates of sprouting and effective fruiting; the cultivar Bonão presents intensity and regularity of flowering; the cultivars Coral and Kampai present the highest intensities and regularities of effective fruiting and; the cultivar Riograndense is the most irregular and unproductive.